2010
DOI: 10.1007/s11926-010-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Hypertension: Cause or Effect?

Abstract: Uric acid was first associated with primary hypertension in 1874, yet its role in this condition remains unclear. Historically, uric acid was thought to be a secondary response to hypertension or its associated conditions. However, more recent experimental and clinical studies suggest that uric acid could have a contributory role in the pathogenesis of elevated blood pressure. More studies are needed to help dissect the potential mechanisms by which uric acid could initiate this response. It remains possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 99 publications
4
90
0
2
Order By: Relevance
“…90,91 However, there is evidence of a potential association between the plasma concentration of uric acid, blood pressure and cardiovascular risk. [92][93][94][95][96] This situation can be explained by the hyperactivity of xanthine oxidase found in hypertension. 21,27 Exogenous antioxidants Vitamin C. Vitamin C is a potent water-soluble antioxidant.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…90,91 However, there is evidence of a potential association between the plasma concentration of uric acid, blood pressure and cardiovascular risk. [92][93][94][95][96] This situation can be explained by the hyperactivity of xanthine oxidase found in hypertension. 21,27 Exogenous antioxidants Vitamin C. Vitamin C is a potent water-soluble antioxidant.…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%
“…3 One of the recently proposed risk factors for hypertension is hyperuricemia. 4 Observational studies have consistently confirmed the association between serum uric acid and incidence of hypertension. 5,6 However, high serum uric acid is associated with comorbidities, such as cardiovascular disease, kidney disease, or diabetes mellitus and antihypertensive medications, that can influence the association of serum uric acid and blood pressure.…”
mentioning
confidence: 94%
“…Our result is similar to that of Bellomo et al, which reported that each increase of 10 mg/l (59 μmol/l) was associated with 23% risk of decreased GFR greater than 2 ml/min/year (after adjustment of confounding factors) in healthy normotensive adults [12]. A randomized clinical trial in hyperuricemic adolescents with hypertension (the decrease in uricemia under allopurinol was related to a decrease in blood pressure) changed the classic design where the cardiovascular drop-risk association in some studies was due to l Gout belongs to the metabolic syndrome [36].…”
Section: Discussionmentioning
confidence: 99%